Impact of participation in rural digital governance on grassroots political trust among high-quality farmers—analysis using survey data from 899 high-quality farmers in Jiangxi Province - Wang, Jiawei; Liu, Kejian; Yuan, Ruolan; Kuang, Xia; Qiu, Hailan (Frontiers in Sustainable Food Systems, 2025)
Rural revitalization cannot be achieved without effective governance. Using the Oprobit model, instrumental variables, moderating-effects model and mediating-effects model, this study investigated the impact of participation in rural digital governance on high-quality grassroots political trust and its mechanism using micro-survey data from 899 high-quality farmers in Jiangxi Province. This study demonstrated that participation in rural digital governance significantly enhances grassroots political trust among high-quality farmers, and both robustness and endogeneity tests yielded consistent conclusions. Further analysis revealed that organizational membership and human expenditure play positive and negative moderating roles, respectively, in the impact of participation in rural digital governance on grassroots political trust among high-quality farmers, and that there are differences in the identity of rural elites in the facilitating effect of participation. Mechanism analysis revealed that participation in rural digital governance promotes grassroots political trust among high-quality farmers by enhancing their subjective social status, and its effect accounts for 11.8% of the total effects. Accordingly, policy recommendations should be made to increase the promotion of rural digital governance, strengthen farmers’ participation and supervision, enhance transparency and effectiveness, support the membership of high-quality farmers’ organizations, reduce the burden of favors and promote overall trust.